The effect of macroeconomic determinants on Malaysian stock market performance / Fatihatunnurrahim Abd Rahim - Abd Rahim, Fatihatunnurrahim (Faculty of Business and Management, 2014)
This paper aims is finding out the effect of macroeconomic determinant on stock market performance in Malaysia. The study is focuses on stock index which is FTSE Bursa Malaysia Kuala Lumpur Composite Index (FBMKLCI). The macroeconomic variables considered are palm oil price, interbank rates (3 month), exchange rates inflation rates and gold prices. The sample of this study comprises of 191 observations each of the independent and dependent variables on a monthly basis over 16 years period from January 1998 to December 2013. Methodology used for this study is by using Multiple Linear Regression with time series data sourced from DataStream and Index Mundi. Thereafter, econometric tests are to be conducted to observe the relationship of the macroeconomic variables to the FBMKLCI. Interactive software package E-view 7 would be used for testing and analyzing the data collected. The study is an attempt to investigate the relationship of the chosen macroeconomic variables towards influencing stock index which is FBMKLCI. Findings from previous research papers mostly on developed markets indicate that macroeconomic variables do play a significant role in the determination of stock returns. The results of this research paper would provide an indicative view and could form an important basis for investors and policy makers in their investment strategies and policy decisions respectively.